Analysis of students’ difficulties in mathematical literacy - T Hapsari; D Dahim; J A Dahlan (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This research investigates the students’ mathematical literacy competence and difficulties in answering the mathematic literacy questions. This study is considered as a survey research. 53 students are participating in this research. The data are collected through the instrument of mathematical literacy competence test. A quantitative analysis is employed to examine the students’ mathematical literacy competence levels. Meanwhile, the qualitative analysis is conducted to figure out the students’ errors in completing the mathematic literacy test. Mathematic literacy is greatly important for students to acquire. Mathematical literacy is an ability to completely master the mathematic concepts and apply them in our daily life. Mathematical literacy competence deals with the ability to formulate, apply, and interprate mathematics in various contexts. The students’ mathematical literacy is considered still poor. The students’ difficulties are identified through the students’ errors in answering the mathematical literacy questions. The students’ errors in answering the mathematical literacy questions respectively from the highest frequency are: errors in understanding, transformation, processes, encoding, and reading. Students’ errors may be utilized as one consideration for the teachers’ anticipation steps to overcome the students’ mathematical literacy difficulties.